EFFECT OF SEEDBED TYPES, UREA FERTILIZER RATES AND INTERCROPPING OF SORGHUM WITH LEGUMES ON STRIGA INCIDENCE AND SORGHUM YIELD - E.J., Kenyi; *, Marchelo-d; P.W, Ragga, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
These studies were conducted at Damazin Research Station, Damazin, (Latitude 11 0 47’34N, longitude 340 21’55 E) and approximately 343.01 meters above sea level (MSL) for two consecutive seasons of 2006/07 and 2007/08. Three types of seed beds were used namely, flat (control 1); normal ridged and tied ridged in a Striga infested field trial. The objectives were to test for the incidence of witch weed (Striga spp.) and performance of sorghum under the different treatments. The treatments were: two rates of urea fertilizers applied at 103.5 and 207.0 kg/ha; four leguminous plants namely, Bambara nuts, (Vigna subterranea L. Verdc.; Groundnuts, (Arachis hypogoea L.); Clitoria, (Clitoria ternatea); and Desmodium spp.) were intercropped with sorghum, Sorghum bicolor L. Moench (cv. Wad Ahmed) and a sole sorghum without any treatment (control 2) were compared for their effect on Striga population at 8 and 12 weeks after sorghum emergence (WASE); Striga dry weight at harvest; sorghum height and sorghum grain and straw yield. Results showed that normal ridged seedbeds reduced Striga population and its dry weight effectively. Amongst the legumes intercropped with sorghum, Clitoria spp. reduced sorghum height considerably, and the application urea fertilizers regardless of the rates used, increased sorghum grain yield as well as Striga population.